Strengthening Data Literacy Among Vocational High School Students Through a Service-Learning-Based Data Science Training Program - Nor Anisa Fauzy; Muhammad Riko Anshori Prasetya; Nurhaeni Nurhaeni; Bayu Nugraha; Ahmad Hidayat (Help: Journal of Community Service, 2026)
Data literacy has become a critical competency in the digital era, particularly for vocational high school students who are expected to meet the evolving demands of data-driven industries. However, many vocational education institutions in Indonesia have not yet adequately integrated data science skills into their curricula, resulting in a gap between educational outcomes and workforce requirements. To address this challenge, a Service-Learning-based community engagement program was implemented to strengthen students’ foundational competencies in data science. This community service program was conducted at SMK Muhammadiyah 3 Banjarmasin and involved 30 students from the Software Engineering Department. Adopting a Service Learning approach, the program consisted of needs assessment, instructional workshops, guided practice sessions, mentoring, and evaluation activities. Training modules covered data science fundamentals, data management and visualization using Microsoft Excel Pivot Tables, and introductory Python programming. Program effectiveness was assessed using a pre-test and post-test design, complemented by participant satisfaction surveys. The findings revealed a substantial improvement in participants’ data literacy competencies. The average score increased from 50.1 in the pre-test to 81.9 in the post-test, representing an improvement of 31.8 points or 63.5%. The highest learning gains were observed in the Microsoft Excel module due to its practical and interactive learning activities. Participant feedback was highly positive, with 92% of students rating the program as good or very good. The results indicate that hands-on and application-oriented learning activities effectively facilitate the acquisition of foundational data science skills among vocational students.